Improving fermentative methane production of glycerol trioleate and food waste pretreated with ozone through two-stage dark hydrogen fermentation and anaerobic digestion. (1st January 2020) - Yue, Liangchen; Cheng, Jun; Hua, Junjie; Dong, Haiquan; Zhou, Junhu; Li, Yu-You
Highlights: Ozonation pretreatment strongly degraded lipids prior to anaerobic digestion. Increasing ozone concentration led to increased methane yield from lipids. Coating of methanogens by lipids was substantially relieved after pretreatment. Ozone (0.02 g-O3 /g-TVS) led to the highest CH4 yield from food waste. Ozone (>0.05 g-O3 /g-TVS) led to a decrease in CH4 yield due to excess oxidation. Abstract: In order to alleviate substantial inhibition of anaerobic digestion by undegraded lipids that coat microorganisms in food wastes, an ozonation pretreatment was employed to degrade the lipids and promote methane production through two-stage dark hydrogen fermentation and anaerobic digestion. GC–MS analysis showed that degradation rate of glycerol trioleate into hexadecanoic acid and tetradecanoic acid increased to 78.6% when ozone concentration increased to 0.8 g-O3 /g-TVS in the pretreatment. SEM and FTIR analysis indicated that coating of methanogens by lipids during the anaerobic digestion process was substantially relieved after ozonation pretreatment. The methane yield from glycerol trioleate after dark hydrogen fermentation increased by 81.9% to 946.5 mL/g-TVS after 0.8 g-O3 /g-TVS pretreatment. When food waste (carbohydrate 45.7%, protein 21.4%, lipid 28.1%) and glycerol trioleate were mixed with a total volatile solids (TVS) ratio of 1:1, an ozonation pretreatment of 0.02 g-O3 /g-TVS gave the highest energy conversion efficiency of 78.7% through two-stage dark hydrogen fermentation and anaerobic digestion. However, excessive ozone (≥0.05 g-O3 /g-TVS) pretreatment decreased not only hydrogen yield but also methane yield, because most small-molecular carbohydrates and a part of proteins were destroyed by ozone oxidization.